REQUIREMENTS FOR MARRIAGE IN POLISH AND FRENCH LAW: SEMANTIC AND SYNTACTIC ANALYSIS - MAZURKIEWICZ, Paulina (Comparative Legilinguistics, 2016)
The objective of this article is to compare semantic and syntactic designation of requirements for marriage in Polish and French law. In both jurisdictions they generally fall into three categories: conditioning, formal and exclusive. The analyses of the terminology pertaining to French and Polish marriage law have exposed similarities and differences in conceptualisation of requirements for marriage. The Polish law allows both of the religious and secular marriage. By contrast, the French law allows for same-sex marriage (mariage homosexuel) and marriage in the event of the absence of one of the future spouses (mariage posthume). The present research has also proved the usefulness of onomasiology and semasiology as combined methods of terminological analysis.